Hubungan Antara Kadar Magnesium Serum Dengan HbA1c Pada Penderita Diabetes Mellitus Tipe 2 Di RSUP Fatmawati Jakarta: Correlation between MagnesiumSerum and HbA1c Levels in Patients with Type 2 Diabetes Mellitus at Fatmawati General Hospital Jakarta - Prasetyorini, Tri; Lestari, Diah; Putri, Wandira Nur Eka (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Diabetes Mellitus (DM) is a collection of symptoms that arise in a person caused by an increase in blood glucose levels due to a progressive decrease in insulin secretion. magnesium (Mg) plays an important role in insulin secretion, insulin binding, and homeostasis. Mg Serum level is an important factor in the etiology and development of macrovascular and microvascular complications in diabetes mellitus patients. HbA1c in DM patients is used to monitor glycemic control and predict the progression of diabetes complications. The purpose of this study was to determine the relationship between serum magnesium and HbA1c levels in patients with type 2 diabetes mellitus. The design of this study was an analytical observational study with a cross-sectional design. The data used are secondary data obtained from patients with type 2 diabetes mellitus at Fatmawati General Hospital for the period 2019 – 2020. The research sample used was 84 data for patients with type 2 diabetes mellitus. Analysis of the data used includes descriptive analysis and then hypothesis testing using the Spearman correlation test. The result of this study showed an association between serum magnesium and HbA1c levels with a value of p = 0,000 (p ≤ 0,05) and r = 0,513. The conclusion obtained in this study is that there is a strong negative pattern relationship between serum magnesium and HbA1c levels in type 2 diabetes mellitus.